Managing high heat flux up to 500 W/cm2 through an ultra-thin flat heat pipe with superhydrophilic wick. (25th July 2017) - Lv, Lucang; Li, Ji
Highlights: An ultra-thin flat heat pipe was developed. The wick was treated to be superhydrophilic. The flat heat pipe can manage heat flux up to 490 W/cm 2 . An extremely low thermal resistance was obtained. Abstract: Miniaturization of high-performance electronics demands heat dissipation components with small size while high performance. This paper presents an ultra-thin flat heat pipe (UTFHP) with a total thickness of 0.95 mm and an inner height of 0.55 mm. Novel wick structure made of superhydrophilic sintered copper mesh screen was employed to provide strong capillary force as well as low flow resistance for the working fluid. Two high-heat-flux heaters were soldered discretely on the UTFHP to evaluate its heat transfer characteristics both under natural air convection and forced water cooling conditions. It is found that the UTFHP had much lower evaporator temperature and much smaller thermal resistance compared with copper sheet, no matter for one heater or two heaters situation, demonstrating excellent heat transfer capability. Moreover, the UTFHP could tolerate 490 W/cm 2 without dryout. The transition heat flux was 302.5 W/cm 2 in term of thermal resistance, at which the minimum thermal resistance was 0.039 °C cm 2 /W, indicating the proposed ultra-thin flat heat pipe can be a promising solution for cooling high power density electronics.